Attitude of University Students and Teachers towards Instructional Role of Artificial Intelligence - Irshad Hussain (International Islamic University Islamabad, 2020)
The present study evaluated the attitude of university students and teachers towards instructional role of artificial intelligence. It was a descriptive study and the researcher used survey approach for data collection. The data was collected from 323 university students and 196 university teachers by using two questionnaires developed (one for students and one for teachers) on five point rating (Likert) scales. Descriptive statistics i.e. percentage was used for data analysis. This study demonstrated positive attitude of university students and teachers towards AI and its instructional role. It appeared to be encouraging for the respondents as well as for the administrators and policy makers. The study suggested higher education institutions to formulate a feasible policy to get benefits of instructional role of AI in higher education.